Music education contributes to development and personal change in young adults with disabilities - Lundqvist-Persson, Cristina; Holmqvist, Gärd (Frontiers in Rehabilitation Sciences, 2022)
In Sweden as in many other countries, there has been increasing recognition of the importance of health, social participation, and active leisure time for people with disabilities. Against this background, a three-year music education was started for a group of young adults with disabilities in order to enhance their wellbeing, learning, and emotional and social development. The aim of the study was to evaluate the results of a 3-year education program with set goals for young adults with disabilities using a qualitative method. The study was conducted from autumn 2014 to 2018. Four semi-structured interviews were conducted with the participants, the first at the beginning of the education, after the first year, second, and third year respectively. The interviews were tape recorded and transcribed verbatim. The teachers and care staff made process notes about the development of each participant. The transcribed interviews and process notes were analyzed using Thematic Content Analysis. The education achieved its purpose and goals as evidenced by participants, teachers, and staff. It showed that music education training may revitalize people with disabilities. Furthermore, it demonstrated that persons with disabilities can learn, develop, and even change on a personal level, if they are given the right conditions.